POWER-PLANT VIBROACOUSTICS IMPACT ON NOISE LEVELS IN FLOATING CRANE CABINS - Elena V. Yegelskaya; Anatoly A. Korotkiy (Advanced Engineering Research)
The experimental results of th e noise spectra in the floating crane cabins under the sound radiation of the IC e ngine power - plant are presented. The frequency ranges when noise levels in the cabins exceed the sanitary norms are shown.